ICT infrastructure, technical and administrative support as correlates of teachers' laptop use - Moses, Priscilla; Abu Bakar, Kamariah; Mahmud, Rosnaini; Wong, Su Luan (Elsevier, 2012)
The purpose of this quantitative study was to explore the facilitating conditions associated with teachers’ laptop use. Questionnaires were collected from 412 teachers. This study found two of the facilitating conditions [technical (r = .171, n = 412, p = .001) and administrative support (r = .213, n = 412, p <.0005)] to have a small but definite relationship with laptop use. The relationship between ICT infrastructure (r = .036, n = 412, p = .463) and laptop use was insignificant. Hence, more emphasis should be given on technical and administrative support to ensure teachers’ use of laptops.